Workload Characterization in Embedded Systems Utilizing Hybrid Intelligent Gated Recurrent Unit and Extreme Learning Machines - Sivaramakrishnan , R.; SenthilKumar, G. (International Journal of Intelligent Systems and Applications in Engineering, 2023)
As the demand for embedded systems continues to rise exponentially, accurately estimating and predicting the necessary resources for these systems remains a significant challenge due to their dynamic workloads. Numerous intelligent algorithms have been developed using machine learning and deep learning techniques, leveraging their computational power and ability to capture workload patterns. However, these algorithms still require further refinement to effectively handle the increasingly diverse and rapidly evolving workloads. This framework aims to design Gated Extreme learning machines for Embedded Workload Characterization (GEEWC) to address the challenges of accurately characterizing and predicting resource requirements in embedded systems, which often operate under dynamic and unpredictable workloads. By combining the Gated Recurrent Unit (GRU) and Extreme Learning Machines (ELM), GEEWC leverages the strengths of both models to improve the accuracy and efficiency of workload characterization and resource prediction. The results of the experimentation show that the suggested framework performs consistently well across all three workload benchmarks such as the Internet of Medical Things (IoMT), EEMBC, and SPARK workloads. The F1-Score, recall, specificity, accuracy, and recall metrics consistently reflect high levels of performance, indicating that the framework is able to effectively handle dynamic workloads. This robustness makes it a reliable solution for real-world scenarios where workloads can vary significantly. Further analysis of the results reveals that the framework is particularly effective in handling the complex IoMT workload, suggesting its suitability for healthcare applications. Moreover, the framework exhibits robustness and scalability, allowing it to handle large datasets and accommodate future growth in the healthcare industry. The results also highlight the framework’s ability to accurately predict and diagnose medical conditions, making it a valuable tool for healthcare professionals. Overall, these findings solidify the framework’s potential for revolutionizing healthcare applications and improving patient outcomes.